2022
DOI: 10.3389/fpls.2021.797958
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Perspectives in the Epigenetics of Climate Change-Induced Forests Decline

Abstract: Forest tree species are highly vulnerable to the effects of climate change. As sessile organisms with long generation times, their adaptation to a local changing environment may rely on epigenetic modifications when allele frequencies are not able to shift fast enough. However, the current lack of knowledge on this field is remarkable, due to many challenges that researchers face when studying this issue. Huge genome sizes, absence of reference genomes and annotation, and having to analyze huge amounts of data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 143 publications
0
15
0
Order By: Relevance
“…Trees are sessile organisms with a long generation time, which makes them vulnerable to climate change and hindered by fast adaptations [ 1 , 2 , 3 ]. The frequency and intensity of drought events are increasing worldwide, triggering extensive dieback and mortality in many forest ecosystems [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trees are sessile organisms with a long generation time, which makes them vulnerable to climate change and hindered by fast adaptations [ 1 , 2 , 3 ]. The frequency and intensity of drought events are increasing worldwide, triggering extensive dieback and mortality in many forest ecosystems [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite scientific evidence supporting the involvement of epigenetic modifications in adaptation and responses to the environment, it is unknown to what extent genetic and epigenetic factors determine important traits related to fitness under these circumstances [ 77 ]. Such knowledge can be translated into biotechnology to address the worrisome increase in tree mortality observed in recent decades [ 78 ].…”
Section: The “Omics” and Their Integration With Other Approaches (How)mentioning
confidence: 99%
“…To cope with the fast-changing climate and novel stresses, populations need rapid responses like phenotypic plasticity to provide the required reproductive success. It has been shown that stresses can modify epigenetic marks and generate a rapid epigenetic response(s) in the form of a wide range of novel and stable ecological phenotypes in just a few generations through gene expression regulation ( Grativol et al, 2012 ; Heer et al, 2018a ; Ashapkin et al, 2020 ; Ashe et al, 2021 ; Baduel et al, 2021 ; Boquete et al, 2021 ; García–García et al, 2022 ). Among all the known epigenetic mechanisms, DNA methylation is relatively stable with transgenerational heritability and contributes importantly to phenotypic variability under stress.…”
Section: Underpinning Of Epigenetic Adaptive Responses In Natural Pop...mentioning
confidence: 99%
“…To sum up, evidence indicates that 1) epigenetic marks lead to phenotypic changes in plants and serve as important drivers to rapidly widen the total phenotypic plasticity and phenotypic variance of natural populations, 2) plant epigenomes show high diversity and rapidly generate responses to external stimuli, 3) epigenetic mechanisms help to provide the required variability for selection and expand the plants’ repertoire of adaptive responses 4) epi-variability creates epialleles, that serve as an additional tier of diversity for adaptive evolution 5) epigenetic variability is amenable to selection and may eventually become heritable, 6) epigenetic and genetic fields may complement each other for better execution of phenotypic plasticity and adaptive responses and 7) various biological processes, ecological factors and habitats strongly influence the epigenetic regulatory processes in natural populations ( Robertson and Wolf 2012 ; Trucchi et al, 2016 ; Amaral et al, 2020 ; Ashapkin et al, 2020 ; Ashe et al, 2021 ; Baduel et al, 2021 ; Boquete et al, 2021 ; Qiu et al, 2021 ; García–García et al, 2022 ). It has been shown that both genetic and epigenetic variations contribute to environmental stress-induced heritable phenotypic divergence.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%